Survival trends in solid cancers in the Nordic countries through 50 years - Hemminki, Janne; Försti, Asta; Hemminki, Akseli; Hemminki, Kari (European journal of cancer (Oxford, England, 2022)
AIMS: Global survival studies in cancer have generally shown favourable development, but studies over extended periods on populations for which medical care is essentially free of charge are lacking. METHODS: We analyse relative 1- and 5-year survival in all solid cancers in Denmark, Finland, Norway and Sweden through a 50-year period (1970-2019) using the NORDCAN database. RESULTS: The most recent survival results showed three types of patterns. Cancers of very good survival (5-year survival ∼90%) included common cancers of the breast and prostate, as well as melanoma. The second pattern, which included the largest number of cancers, showed 1-year survival of over 80% and a drop of 10-20 % units in 5-year survival. The third group consisted of eight fatal cancers, sharing poor 5-year survival (around 20%). The 50-year improvement in 1-year survival was largest (30-50 % units) in kidney, brain, gallbladder and liver cancers, and (∼30%) in colon, small intestinal, lung, pleural, pancreas and ovarian cancers. Improvements in 5-year survival were highest (40-50 % units) in prostate and kidney cancers but remained at 10-20 % units for the eight fatal cancers. Survival showed significant sex preferences for a few cancers. CONCLUSIONS: The analysis over a half-century confirms the progress in 'real-world' cancer control, and in 84% of patients 5-year survival was >60%. Metastases remain a challenge, placing the emphasis on early detection before metastasis occurs. Novel therapies, such as immunotherapy which has curative potential even against metastatic disease, are needed.
Keywords: analýza přežití; Liver Neoplasms; Scandinavian and Nordic Countries; Dánsko; Cancer control; nádory jater; Finsko; Age Distribution; Incidence; Survival Analysis; Prognosis; Skandinávie a severské státy; registrace; mužské pohlaví; Periodic survival; incidence; míra přežití; Registries; Follow-Up Studies; následné studie; Treatment; ženské pohlaví; Humans; věkové rozložení; Survival Rate; Finland; rizikové faktory; Female; Risk Factors; Denmark; lidé; Male